The main directions of increasing the reliability of gas distribution systems in high-rise districts - Zhila Viktor; Solovyeva Elena (MATEC Web of Conferences, 2018)
The main source of energy in the economy is gas fuel. The specific weight of natural gas in the fuel and energy balance is about 50%. †The main requirement for the gas distribution system is to ensure the reliability, safety of this system. One of the ways to improve the reliability of gas supply systems is to use the reliability of automatic equipment to determine the gas contamination of premises. Based on the analysis of calculation formulas, an algorithm for the hydraulic calculation of gas pipelines is compiled. Based on the characteristics of gas distribution systems, it is advisable to apply such a solution, when gas supply of domestic consumers, boiler houses of municipal agricultural enterprises is carried out from the distribution network of high and medium pressure through autonomous combined pressure regulators installed in areas of high-rise buildings.